Reabertura política e movimento negro: a revista/jornal tição e a circulação das reivindicações negras promovidas em Porto Alegre nos anos finais da ditadura civil-militar (1978-1980) - Maria, Stella Bianca Ferreira (2021)
This research proposes to analyze through the magazine / newspaper Tição the discourse produced by the Black Movement located in the city of Porto Alegre / RS, in the final years of the civil-military dictatorship, specifically between the years of 1978 and 1980. The proposed time frame in the work is justifies by the circulation time that this communication material has, constituting two magazines, annual in 1978 and 1979 respectively, and a newspaper, in its last year of circulation, in 1980. Through Tição we investigate the debate proposed by this black organization located in the south of Brazil; as well as we also investigated the debates that were consensus among the diverse black organizations spread throughout Brazilian territory. By understanding that the black movement is not constituted as a homogeneous bloc, but is identified by its basic concern on the racial issue, we seek to understand how the process of “democratic resistance”, which includes black movements, was constituted beyond of the great black national front, the MNU. We therefore seek to demonstrate the existence of a black movement in the city of Porto Alegre since the 1970s, as we also intend to manifest, through the documents produced by Organs repressive organs, the monitoring that occurred on the material and its editors, as well as reflect on the considerations left to its readers and the editors who produced it.